2012
DOI: 10.1063/1.3681331
|View full text |Cite
|
Sign up to set email alerts
|

In situ study of the growth properties of Ni-rare earth silicides for interlayer and alloy systems on Si(100)

Abstract: We report on the solid-phase reaction of thin Ni-rare earth films on a Si(100) substrate, for a variety of rare earth (RE) elements (Y, Gd, Dy and Er). Both interlayer (Ni/RE/) and alloy (Ni-RE/) configurations were studied. The phase sequence during reaction was revealed using real-time x-ray diffraction whereas the elemental diffusion and growth kinetics were examined by real-time Rutherford backscattering spectrometry. All RE elements studied exert a similar influence on the solid phase reaction. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…They reported that the Ni silicide stability could be improved, especially with alloying elements such Pd, Pt, W, Rh, Mo and Ta. Other methods have been used to introduce the alloying element such as interlayer, capping layer or sandwich configuration [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the Ni silicide stability could be improved, especially with alloying elements such Pd, Pt, W, Rh, Mo and Ta. Other methods have been used to introduce the alloying element such as interlayer, capping layer or sandwich configuration [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] Consequently, Ni silicide with an interlayer of another metal can be considered important not only to improve thermal stability but also to modify the Schottky barrier height of Ni silicide for conventional MOSFETs and SBMOSFETs. Although there have been some studies about Ni silicide with an Er interlayer, 30,31) the electrical characteristics of this structure has not been investigated in depth. Moreover, Ni silicide with an interlayer in a different position has rarely been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Demeulemeester et al, studied the Ni-REMs (Y, Gd. Dy and Er) Silicides formation properties and their effect on SBH modulation 20 . Ishikawa et al, has shown the decrease in work function of PtSi from 4.92 to 4.57 eV using Yb interlayer 21 .…”
mentioning
confidence: 99%